2013
DOI: 10.1007/s13300-013-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Insulin Aspart in Basal-Bolus Regimens Regardless of Age: A1chieve Study Results

Abstract: IntroductionHypoglycemia is a complication in the management of type 2 diabetes, and elderly people are at greater risk of experiencing hypoglycemia events than younger patients. Insulin analogs achieve glycemic control with minimal risk of hypoglycemia and may therefore be a good treatment option for all patients.MethodsA1chieve was an international, multicenter, prospective, open-label, non-interventional, 24-week study in people with type 2 diabetes who started/switched to therapy with biphasic insulin aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
2
2
0
2
Order By: Relevance
“…The efficacy and safety of treatment intensification in the elderly is critical because of the aging population and higher prevalence of type 2 diabetes in this group (23). These findings are consistent with those of the A 1 chieve study and show that a basalbolus therapy can be initiated in the elderly without increased risk of hypoglycemia (24). Moreover, in a pooled analysis, Lee et al (25) described that adding insulin GLA in an elderly patient population had low rates of hypoglycemia with decreases in HbA 1c similar to those in younger patients; however, AUTONOMY expanded on these results to demonstrate that therapy intensification and self-titration, starting with a single prandial dose of lispro, can safely occur in the elderly.…”
Section: Discussionsupporting
confidence: 90%
“…The efficacy and safety of treatment intensification in the elderly is critical because of the aging population and higher prevalence of type 2 diabetes in this group (23). These findings are consistent with those of the A 1 chieve study and show that a basalbolus therapy can be initiated in the elderly without increased risk of hypoglycemia (24). Moreover, in a pooled analysis, Lee et al (25) described that adding insulin GLA in an elderly patient population had low rates of hypoglycemia with decreases in HbA 1c similar to those in younger patients; however, AUTONOMY expanded on these results to demonstrate that therapy intensification and self-titration, starting with a single prandial dose of lispro, can safely occur in the elderly.…”
Section: Discussionsupporting
confidence: 90%
“…В данном исследовании первая инъекция прандиального инсулина вводилась перед за-втраком и в дальнейшем, при необходимости, пациентам добавлялась 2-я или 3-я инъекция перед обедом и ужином, титрация осуществлялась по уровню гликемии перед сле-дующим приемом пищи. Результаты этого исследования согласуются с ранее представленными данными [26] о том, что стратегия постепенного добавления прандиального инсулина к базальному может безопасно использоваться у категории пожилых пациентов с СД2, поскольку в ис-следовании AUTONOMY в подгруппе пациентов ≥65 лет инициация терапии прандиальным инсулином не проде-монстрировала повышения риска развития гипогликеми-ческих реакций [24]. В данном исследовании у пациентов имело место увеличение массы тела независимо от того, какой алгоритм титрации использовался; однако в груп-пе пациентов, проводивших титрацию инсулина раз в три дня (Q3D), была отмечена несколько большая прибавка массы тела.…”
Section: исследование Autonomyunclassified
“…В этой стратегии также использованы общие принци-пы самостоятельного измерения глюкозы крови натощак перед завтраком, минимизируя таким образом потреб-ность в дополнительных точках самоконтроля в течение дня. Еще одним преимуществом данного подхода являет-ся удобство выполнения инъекции в домашних условиях, что позволяет пациентам контролировать гликемию на-тощак утром с целью улучшения гликемического контро-ля в течение дня [26]. Как и в исследованиях AUTONOMY и FullSTEP, в исследовании START пациентам перед добав-лением инъекций прандиального инсулина были оптими-зированы дозы базального инсулина [27].…”
Section: исследование Startunclassified
“…In two large observational studies, HbA 1c , PPG and fasting plasma glucose (FPG) levels were significantly reduced after switching to insulin aspart, one in which patients used insulin aspart with a basal insulin [ 87 ], and another in which basal insulin was not used [ 88 ]. In both studies, oral antidiabetic drugs (OADs) were allowed.…”
Section: Clinical Efficacy Of Insulin Aspartmentioning
confidence: 99%
“…The A 1 chieve observational study in patients who started or switched to basal–bolus therapy with insulin aspart has demonstrated reduced risk of hypoglycemia in people aged ≤40, 40–65, and >65 years [ 87 ] (Table 4 b). Another analysis of the A 1 chieve study, examining 2026 patients using insulin aspart as the only insulin treatment, indicated that both insulin-naïve and insulin-experienced patients had reduced risk of overall hypoglycemia after adding insulin aspart to their treatment regimen [ 88 ].…”
Section: Safety and Tolerability Of Insulin Aspartmentioning
confidence: 99%